COMÉRCIO DE PEIXES UTILIZADOS COMO ISCA-VIVA - ROMERO, João Pedro Alves,; ACUNHA, Rubia Mara Gomes,; SILVA, Maria Eduarda Vasconcelos Mendes,; ALMEIDA, Rômullo Guilherme,; COSTA, Deliane Cristina,; CAMPOS, Cristiane Meldau de, (ANAIS DO ENIC, 2023)
-